1995
DOI: 10.1016/0091-3057(94)00394-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sertindole on sleep-wake states, electroencephalogram, behavioral patterns, and epileptic activity of rats

Abstract: COENEN, A. M. L., N. ATES, T. SRARSFELDT AND E. L. J. M. VAN LUIJTELAAR. Effects of sertittdole onsleep-wake states, electroencephalogram. behavioral potterns, and epileptic activity of rats. P HARMACOL BIOCHEM BEHAV 51(2/3) 353-357, 199X-In this study we addressed the effects of the S-HT, receptor antagonist sertindole in rats.The compound was administered in doses of 0.08. 0.32, and 1.28 mg/kg, whereas a control group received the solvent. The effects of sertindole on sleep-wake states, behavioral patterns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…However, there was no significant slowing of the background electroencephalogram after sertindole administration. Additionally, sertindole was not found to have any effects on epileptic spike-wave discharges [7]. Thus, the previous study in rats as well as ours in patients with schizophrenia support the conclusion that in comparison to the majority of other antipsychotics, sertindole has a low propensity to increase SWA and epileptiform discharges in EEG.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, there was no significant slowing of the background electroencephalogram after sertindole administration. Additionally, sertindole was not found to have any effects on epileptic spike-wave discharges [7]. Thus, the previous study in rats as well as ours in patients with schizophrenia support the conclusion that in comparison to the majority of other antipsychotics, sertindole has a low propensity to increase SWA and epileptiform discharges in EEG.…”
Section: Discussionsupporting
confidence: 81%
“…To our best knowledge, this study is the first to report EEG changes during sertindole treatment in patients with schizophrenia. We found only 1 previous study in the literature that investigated effects of sertindole on sleep-wake states, behavioral changes, EEG recordings, and epileptic activity in rats [7]. It showed that sertindole mildly increases slow wave sleep and suppresses REM sleep in relation to its antagonistic activity at serotonergic 5-HT2 receptors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation